Image analysis and recognition : 14th International Conference, ICIAR 2017, Montreal, QC, Canada, July 5-7, 2017, Proceedings /: 14th International Conference, ICIAR 2017, Montreal, QC, Canada, July 5-7, 2017, Proceedings. (2017) - Unknown
No abstract available